Analisis Rasio Profitabilitas Untuk Menilai Kinerja Keuangan Pada PT.Telkom Indonesia - Rismart, Angga heryan (EKALAYA : Jurnal Ekonomi Akuntansi, 2023)
The increase in net profit from 2020 to 2021 shows positive profitability growth. This indicates that PT Telkom Indonesia (PERSERO) Tbk has succeeded in increasing its operational efficiency, increasing revenue, or reducing ineffective costs. However, the decline in net profit in 2022 indicates changes in conditions or factors that influence the company's performance. It is important to pay attention to the company's net profit trends and conduct further analysis to understand the causes of changes in performance. The aim of this research is to analyze the profitability ratio of PT Telkom Indonesia (Perseroan) Tbk for the 2021-2022 period. Profitability indicators are used to evaluate a company's economic results. The data used in this research is secondary data in the form of financial reports published by PT Telkom Indonesia (company) Tbk for the 2021-2022 period which are available on the Indonesia Stock Exchange (BEI) or www.idx.co.id. The results obtained were PT. Telekomunikasi Indonesia Tbk needs to pay attention to factors that can have a significant influence on the assessment of the Company's financial performance, both in terms of GPM, NPM, ROE and ROA in the long term.